Kajian potensi Lahan dan Prospek Pengembangan Beberapa Komoditas Pertanian di dataran Tinggi Napu Kabupaten Poso - Budi Utomo Mondolu; Johannes E.X. Rogi; Johan Rombang (COCOS, 2013)
SUMMARY IDevelopment of the agricultural sector in the Highlands Napu based on the potentialand prospects of the development of agricultural land is not maxiEized, becausemanagement saw the pot"ntiut of less farm land but only at thE prospect ofcommodities so that the land does not produce potentially imposed on certaincommodities. The management of other agricultural land but only saw the potential ofnot reviewing the outlook for the market may lead to difficult for farrners to markettheir production land. Relationship potential and prospects of the development ofagricultural land can affect the production of several agricultural commodities.Potential development of land in accordance with the production of agriculturalcommodities will increase the prospects of better agricultural development. Thepurpose of this study is to assess the potential of land and development prospectsAgriculture of some commodities in the Highlands Nup,r, Poso district.Research methodology used is the field of survey research methods andlaboratory analysis methods as well as analysis of agricultural commodity 4. Potentialassessed land based on field survey equipped with GPS and use of laboratory analysisof the primary data and then analyzed with analysis consisted of location LocationQuotien (LQ); quotients Localization (LO) and quotients Specialization (KS) usingsecondary data obrtained from some institutions associated with research. Analysis ofthe prospects for agricultural development consisting of paddy rice, maize, cabbageand tomatoes using analysis of supply (production trend and the trend of land area),and the Economic Analysis (the ratio of R / C) Z 1.The results showed that agricultural land Plateau Napu Poso production anddevelopment prospects of agricultural commodities is less than optimal because it hasa land suitability class 52 and 53. Paddy rice, maizg cabbage and tomatoes can yieldoptimal production if done countermeasures limiting factors of agricultural landsuitability. Based on land unit No. I and II prospected best value is on tomatoescommodity, land unit No. I1 and III prospected best value on cabbage commodity,land unit No. IV, V, V[, VII prospected best value on Paddy rice commodity. Maizecommodities has been inconstant value from more land unit. Maize commodities hasbeen to be a support for others commodity. From this study it can be concluded thatthe potential of land Plateau Napu have land suitability categories 52 and 53 asinfluenced by certain limiting factors, to increase agricultural production anddevelopment prospects of the limiting factors of land suitability can be addressedproperly. Suggestions can be submitted namely: farmers need to pay attention to thefactors limiting agricultural land suitability, such as alternative penang&ulanan veryhigh rainfall in a'ivay good drainage, nutrient retention by appropriate fertilizationand crop rooting medium with a good way of cultivation